EVALUATION OF INCLUSIVE EDUCATION PROGRAM IMPLEMENTATION - Sindidah HUMAIROH; Connie CHAERUNNISA; M. Suryadi SYARIF (Journal of Education and Leadership in Education, 2022)
This study aims to evaluate the inclusive education program at SDN 14 Jatinegara Kaum, East Jakarta. Descriptive qualitative research method with the CIPP model (context, input, process, product). Sources of informants consisted of school principals, Curriculum/Student Affairs Section, Special Assistance Teachers, Shadow Teachers, Class Teachers, Guardians of Inclusive Students. Research using interviews, observation, documentation. Then the data were analyzed by reduction, presentation and conclusion. Based on the research, the results were obtained: In the context aspect, Vision, mission and objectives are not yet in favor of inclusive students. In the input aspect, financing and infrastructure do not support the inclusion program. In the process aspects of the teaching and learning process and assessments are not maximized, inclusion students still experience difficulties in following learning and the assessment process are still the same as regular students. In the product aspect the results of the inclusive program research are not maximized, because they place more emphasis on non-academic (self-help, social development) but there are still deficiencies in reading development and menus.